CURRENT TRENDS IN THE DEVELOPMENT OF BUSINESS EDUCATION IN RUSSIA - Larisa V. Kartashova; Aleksandra V. Petrovskaya (Вестник Российского экономического университета имени Г. В. Плеханова)
In conditions of fast changing business environment and high competition on the Russian market of business education the necessity of studying and taking into account the needs  and interests of principle stakeholders, i. e. program participants, employers and business schools is becoming more and more topical in order to implement programs of training managers in Russian business schools. The article discusses this issue by considering  one promising direction in training managerial personnel – training professional managers  by the program ‘Master of Business Administration’ (MBA). By analyzing Russian  and overseas research the authors show the most important features of the generation  that today and in the near future will represent the majority of learners in MBA programs,  their attitude to forms of training and subjects being taught; summarize recommendations  of employers in the field of knowledge, skills and competences necessary for successful executives; study the latest developments of international business schools and their introduction in Russian practice and put forward proposals dealing with improvement  of programs for managers’ training, increasing their contribution to ensuring sustainable development of Russian economy and social sphere.